(3bUjOI aj eOM CejQs - (3eMeO Hf eMehO GdYdhj GdJQcRj GdTfbjWjs
(3ChdgG (B:s
(3MeOGk deGdc haj GdLh hGdSad Ke GdUdGI Ydi ebOe GdQSd s
(3BNQgG (B:s
(3Udi GdEdg Ydi GdeHYhK ef eUQ Ydi eQhQ djGdj GdOgQ hGdOhd s
(3Vef eLehY , JQJjHgG (B: (3UaMI (B153 (3abWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B117 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B((3c (B644) s
Keywords: (3GdCOHs